Aptamer-Based Fluorescence Polarimetric Assay for the Sensitive Detection of Immunoglobulin E in Human Serum - Qin, Xiaohuan (Asian Journal of Chemistry, 2014)
A highly sensitive and selective fluorescence polarization method was developed for the determination of immunoglobulin E based on the aptamer specificity binding immunoglobulin E event into a detectable fluorescence polarization signal. Using this method, the levels of immunoglobulin E in human serum from healthy donors were determined. The results show that the fluorescence polarization method has excellent specificity against target protein and high sensitivity in complex medium and is applicable to the no-separation based detection of proteins in biological sample.